1978
DOI: 10.1017/s0033291700014306
|View full text |Cite
|
Sign up to set email alerts
|

Hypotheses linking neuroses with premature mortality

Abstract: SYNOPSISThe death risk for psychiatric patients has decreased over the last 30 years but still remains higher than that of the general population. The death risk for patients with a diagnosis of neurosis is higher than that for the general population. Previous studies are enlisted to investigate this mortality for socio-economic characteristics, alcohol and drug abuse, psychopathy and accident proneness. Possible psychosomatic aetiology of disease and subsequent death is examined. Psychological theories for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…It is well documented that neurosis treated in psychiatric hospital is associated with increased mortality (Sims, 1978;Sims & Prior, 1978). However, there is little evidence that this phenomenon extends to neurosis managed in general practice.…”
Section: Discounted Future Earningsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that neurosis treated in psychiatric hospital is associated with increased mortality (Sims, 1978;Sims & Prior, 1978). However, there is little evidence that this phenomenon extends to neurosis managed in general practice.…”
Section: Discounted Future Earningsmentioning
confidence: 99%
“…However, there is little evidence that this phenomenon extends to neurosis managed in general practice. Sims (1978) observed that the risk of mortality increased with the severity of neurotic disorder. Therefore, we assumed that the presence of neurotic disorder did not imply an increased likelihood of premature mortality.…”
Section: Discounted Future Earningsmentioning
confidence: 99%
“…Kendler has considered that genetic factors are important in mortality from trauma (suicide and accident) and those with schizophrenia and from diseases (natural causes) among those with neurotic conditions.24 Psychiatric illness and physical conditions resulting in death may be linked in three ways: the mentally ill may have an increased exposure to known causes ofdisease or death-for example, tobacco, alcohol, and dangerous driving; for a given degree of environmental exposure they may have an increased susceptibility to develop illness (psychosomatic disorder); and mental illness may adversely affect the outcome of a physical disease. 25 The excess mortality could be accounted for by several different psychological theories. The cluster theory suggests that illnesses tend to cluster in different bodily and psychological systems in the same individual, that there is a higher concentration of some illnesses in a minority of the population, and that several illnesses tend to occur within a few years of the whole life span.26 The affect of hopelessness may be associated with the early stages of a severe physical illness,27 and many studies have looked at the association between adverse life events and the subsequent onset of serious illness and death.2' The experience of loss has been related to increased mortality,-' and the inability to communicate distressing emotion verbally (alexithymia) may be related to the onset of physical illness.30 Type A behaviour patterns, with competitive striving, aggressiveness, hostility, and continuous working to time limits, have been related to an increased incidence of coronary heart disease.3' Very different life stresses may result in a common pathological pattern of illness resulting in death,32 and in certain predicaments the untoward event has had a last straw effect, resulting in premature death.33 Associations have-also been sought between abnormal psychological states and accident proneness.34…”
mentioning
confidence: 99%
“…The increased mortality risk associated with severe forms of neurotic illness has been especially studied by Sims [1976Sims [ , 1978, Sims and Prior [1978] and Sims and Rudge [1979], In a follow-up of 1,482 patients pre viously treated in hospital for neurosis, they found the combined relative death risk from nervous, circulatory and respiratory diseases to be 1.6 in comparison with the general pop ulation.…”
Section: Discussionmentioning
confidence: 99%